1320. Pharmacokinetics of Isavuconazole Administered as Isavuconazonium Sulfate Intravenous Solution via Nasogastric Tube or Orally in Healthy Volunteers. (31st December 2020) - Desai, Amit; Helmick, Melanie; Heo, Nakyo; Moy, Selina; Stanhope, Stephen; Goldwater, Ronald; Martin, Nancy
Abstract: Background: Nasogastric (NG) tube feeding is most common in the intensive care unit and is also used for cancer patients who are unable to eat (e.g. patients with mucositis) or do not want to eat due to severe nausea 1 . For such critically ill patients with invasive fungal infections, administration of isavuconazonium sulfate (ISAVUSULF) via NG tube can be an alternate route of drug administration. Methods: This was a randomized, open-label, 2-period, 2-sequence single dose crossover study in healthy male and female subjects. Each subject participated in 2 treatment periods separated by a washout of at least 30 days between investigational product administrations in each period. Subjects were administered a single dose of 372 mg ISAVUSULF intravenous (IV) solution via NG tube (test formulation) or 372 mg ISAVUSULF capsules for oral (PO) administration (i.e., PO capsules administered to subjects without NG tube) (reference formulation) under fasting conditions on day 1 of each period. Pharmacokinetic (PK) samples were collected predose on day 1 of each period and at multiple time points postdose through day 21. Standard safety and tolerability assessments were conducted in each period. Results: Eighteen subjects were randomized in this study and 13 provided concentrations in both sequences that were PK evaluable. The analysis of variance estimate (Table 1) of the study population suggests that the isavuconazole IV NG tube administration geometric least-square (LS) mean values of the observed maximum concentration (Cmax ), area under the plasma concentration-time curve (AUC) to the last measurable concentration (AUClast ), AUC to time infinity (AUCinf ), and AUC from start of dosing to 72 hours (AUC72 ) were 105.3%, 97.6%, 99.3% and 97.8%, respectively, of the corresponding oral administration values. The geometric LS mean ratio and 90% Confidence Intervals for the Cmax, AUClast, AUCinf, and AUC72 are completely contained within the prespecified limits of 80% to 125%. There were no deaths or serious adverse events that led to withdrawal of treatment during the conduct of the study. Table 1 Conclusion: The study met its primary endpoint of bioequivalence between the two routes of administration in this population. Both routes of administration are well tolerated. Reference 1 Disclosures: Amit Desai, PhD, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc) Melanie Helmick, BA, Clinical Research, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc) Nakyo Heo, PharmD, MS, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc) Selina Moy, BS, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc) Stephen Stanhope, PhD, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc) Ronald Goldwater, MDCM, Astellas Pharma Inc. (Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc. Parexel International received fees for research support from Astellas Pharma Global Development Inc.)Parexel International (Employee, Employee of Parexel International) Nancy Martin, MD, PharmD, Astellas Pharma Inc. (Employee, Other Financial or Material Support, This study was initiated and sponsored by Astellas Pharma Global Development Inc)